AI Implementation to Enhance Creativity in Designing Book Covers at SMK YP Fatahillah 1 Kramatwatu - Widyawati Widyawati; Eka Ramadhani Putra Putra; Selly Septiani (Alesha Media Digital, 2026)
This community service program was motivated by the low confidence and creativity of students in designing book covers, particularly due to limited technical drawing skills and a lack of understanding of digital technology. In fact, visual design skills are essential for vocational high school students who must be prepared to face the development of creative technology. To address these challenges, this program introduced the use of Artificial Intelligence (AI), specifically Generative AI through platforms such as Canva and ChatGPT, as tools to enhance students’ creativity and ability to visualize their ideas. The method used in this program was a hands-on workshop that included an introduction to basic AI concepts, practice in creating prompts, and the application of AI to generate images and design book covers. The results show that students were able to produce more creative, varied, and conceptually aligned book cover designs. In addition, students gained a better understanding of AI as a creative assistant rather than a replacement for designers. This program demonstrates that integrating AI into the design learning process effectively enhances students' creativity and productivity. These findings are important as recommendations for implementing AI in vocational education environments to support more innovative and technologically relevant learning